2015
DOI: 10.1111/j.1728-4465.2015.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Female Sex Workers' Experiences with Intended Pregnancy and Antenatal Care Services in Southern Tanzania

Abstract: Understanding the pregnancy experiences of female sex workers (FSWs), especially in the context of high rates of HIV and sexually transmitted infections (STIs), is essential to tailoring services to meet their needs. This study explores FSWs' experiences with intended pregnancy and access to antenatal care and HIV testing in two regions of Tanzania. Thirty in-depth interviews and three focus group discussions were conducted. FSWs sought to become pregnant to gain respect as mothers, to avoid stigma, and/or to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
106
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(117 citation statements)
references
References 46 publications
4
106
0
2
Order By: Relevance
“…Although there have been a few studies [30–32]on FSW’s ANC practices, there is a lack of information on the number of ANC visits or the type of care. In one study in India, FSWs reported HIV testing during pregnancy; other studies by Beckham et al and Willis et al described barriers to ANC services mainly due to discrimination or unfriendly behavior of healthcare providers [30–32]. Our study further added that almost all FSWs reported at least one pregnancy complication.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been a few studies [30–32]on FSW’s ANC practices, there is a lack of information on the number of ANC visits or the type of care. In one study in India, FSWs reported HIV testing during pregnancy; other studies by Beckham et al and Willis et al described barriers to ANC services mainly due to discrimination or unfriendly behavior of healthcare providers [30–32]. Our study further added that almost all FSWs reported at least one pregnancy complication.…”
Section: Discussionmentioning
confidence: 99%
“…[58][59][60] The need to provide for children may push some women into sex work, while other women may plan to conceive as an attempt to solidify a partnership and/or leave sex work. 61,62 Women may also desire children for a multitude of reasons independent of their occupation as sex workers. 61 Furthermore, among women not desiring pregnancy, sex work is an occupational risk for unintended pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…61,62 Women may also desire children for a multitude of reasons independent of their occupation as sex workers. 61 Furthermore, among women not desiring pregnancy, sex work is an occupational risk for unintended pregnancy. 63 Despite limited recognition that sex workers are often mothers, health risks associated with sex work make fertility-related research within this population important.…”
Section: Resultsmentioning
confidence: 99%
“…Sex worker -tailored and sex worker -led services that include peer-led and outreach components are pivotal to improving access to HIV/SRH services 41 . This is particularly important given sex workers' accounts of displacement and avoidance of health services due to police enforcement 42 , stigma 40 , and poor treatment by health care staff 43,44 . Additionally, to develop workplace models that better support sex workers' sexual and reproductive health, future research needs to better elucidate the role of sex work venues on HIV and pregnancy prevention.…”
mentioning
confidence: 99%
“…The co-occurrence of both pregnancy and HIV highlight the potential for mother-to-child transmission of HIV (among sex workers who decide to keep their children), and points to a need for improved access to sex worker-tailored and sex worker-friendly Prevention of Mother to Child Transmission (PMTCT) Services integrated into existing HIV services. Qualitative research from Tanzania sheds light on some of the barriers faced by pregnant sex workers in accessing antenatal services, including stigma related to sex work and being pregnant out of wedlock 40 . Taken together, these findings indicate a high level of unmet reproductive need among women sex workers in conflict-affected Uganda.…”
mentioning
confidence: 99%